Standardized Transportation of Human Islets: An Islet Cell Resource Center Study of more than 2, 000 Shipments. Issue 7 (July 2013) - Kaddis, John S.; Hanson, Matthew S.; Cravens, James; Qian, Dajun; Olack, Barbara; Antler, Martha; Papas, Klearchos K.; Iglesias, Itzia; Barbaro, Barbara; Fernandez, Luis; Powers, Alvin C.; Niland, Joyce C.
Preservation of cell quality during shipment of human pancreatic islets for use in laboratory research is a crucial, but neglected, topic. Mammalian cells, including islets, have been shown to be adversely affected by temperature changes in vitro and in vivo, yet protocols that control for thermal fluctuations during cell transport are lacking. To evaluate an optimal method of shipping human islets, an initial assessment of transportation conditions was conducted using standardized materials and operating procedures in 48 shipments sent to a central location by eight pancreas-processing laboratories using a single commercial airline transporter. Optimization of preliminary conditions was conducted, and human islet quality was then evaluated in 2, 338 shipments pre- and postimplementation of a finalized transportation container and standard operating procedures. The initial assessment revealed that the outside temperature ranged from a mean of −4.6 ± 10.3°C to 20.9 ± 4.8°C. Within-container temperature drops to or below 15°C occurred in 16 shipments (36%), while the temperature was found to be stabilized between 15°C and 29°C in 29 shipments (64%). Implementation of an optimized transportation container and operating procedure reduced the number of within-container temperature drops (£15°C) to 13% ( n = 37 of 289 winter shipments), improved the number desirably maintained between 15°C and 29°C to 86% ( n = 250), but also increased the number reaching or exceeding 29°C to 1% ( n = 2; overall p < 0.0001). Additionally, postreceipt quality ratings of excellent to good improved pre- versus postimplantation of the standardized protocol, adjusting for preshipment purity/viability levels ( p < 0.0001). Our results show that extreme temperature fluctuations during transport of human islets, occurring when using a commercial airline transporter for long distance shipping, can be controlled using standardized containers, materials, and operating procedures. This cost-effective and pragmatic standardized protocol for the transportation of human islets can potentially be adapted for use with other mammalian cell systems and is available online athttp://iidp.coh.org/sops.aspx .